MRI in Pseudotumor Cerebri - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The MRI has been used to clarify the pathophysiology of pseudotumor cerebri in seven children, aged between six months and 13 years, reported from British Columbia's Children's Hospital, Vancouver.